2014
DOI: 10.1039/c3dt52288a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced near-infrared photocatalysis of NaYF4:Yb, Tm/CdS/TiO2composites

Abstract: The previous works by our group (Chem. Commun., 2010, 46, 2304-2306; ACS Catal., 2013, 3, 405-412; Phys. Chem. Chem. Phys., 2013, 15, 14681-14688) have reported the near-infrared-driven photocatalysis of broadband semiconductor TiO2 or ZnO that was combined with upconverting luminescence particles to form a core-shell structure. However, the photocatalytic efficiency is low for this new type of photocatalysts. In this work, NaYF4:Yb,Tm/CdS/TiO2 composites for NIR photocatalysis were prepared by linking CdS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 42 publications
2
50
1
Order By: Relevance
“…The increment in photocurrent was ascribed to the UC emission from the UC layer as well as the defect absorption by localized states in amorphous silicon. [245][246][247][248][249] There are generally two different strategies to incorporate the UC ion pairs into the different types of photocatalysts. 238,239 Similar to the Si-based solar cells, the incorporation of UC phosphor into TiO 2 -based dye sensitized solar cells (DSSCs) as well as polymer based cells also demonstrated enhanced NIR response.…”
Section: Utilization Of Nir Light In Solar Cells By Ucmentioning
confidence: 99%
See 1 more Smart Citation
“…The increment in photocurrent was ascribed to the UC emission from the UC layer as well as the defect absorption by localized states in amorphous silicon. [245][246][247][248][249] There are generally two different strategies to incorporate the UC ion pairs into the different types of photocatalysts. 238,239 Similar to the Si-based solar cells, the incorporation of UC phosphor into TiO 2 -based dye sensitized solar cells (DSSCs) as well as polymer based cells also demonstrated enhanced NIR response.…”
Section: Utilization Of Nir Light In Solar Cells By Ucmentioning
confidence: 99%
“…Under simulated solar light irradiation, the system yields a maximum QE of 9.12%, which manifest a 32.7% enhancement as compared to the bare TiO 2 (P25) anode (Fig. [247][248][249] The combination of a UC phosphor with semiconductors like TiO 2 and CdSe can also be used for water splitting under NIR light irradiation in a photoelectrochemical cell. The problem with this system is that the typical red UC emission by the transitions of Er 3+ ( 4 F 9/2 -2 I 15/2 ) at 650 nm cannot be absorbed by the dye in the cell.…”
Section: Utilization Of Nir Light In Solar Cells By Ucmentioning
confidence: 99%
“…3, and corresponding band gap energy (in the inset of Fig. 3) are calculated by following formula [21]:…”
Section: Resultsmentioning
confidence: 99%
“…co-doped Sr 2 SiO 4 :Eu yellow phosphor was composited with TiO 2 [16], it was revealed that the thin and uniformly TiO 2 coating led to an increase in the photoluminescence efficiency. Up-conversion phosphor NaYF 4 :Yb [5,17,18] was also used to support TiO 2 to prepare a near-IR light-driven photocatalyst. All this research has implied an increase of the catalytic activity without light irradiation.…”
Section: Introductionmentioning
confidence: 99%